The sexual history of the global South sexual politics in Africa, Asia and Latin America - Wieringa, Saskia 1950-.; Sivori, Horacio Federico (London Zed Books, 2013)
"The Sexual History of the Global South explores the gap between sexuality studies and post-colonial cultural critique. Featuring twelve case studies, based on original historical and ethnographic research from countries in Africa, Asia, and Latin America, the book examines the sexual investments underlying the colonial project and the construction of modern nation-states. Covering issues of heteronormativity, post-colonial amnesia regarding non-normative sexualities, women's sexual agency, the policing of the boundaries between the public and the private realm, sexual citizenship, the connections between LGBTQ activism and processes of state formation, and the emergence of sexuality studies in the global South, this collection is of great geographical, historical, and topical significance."--Publisher's website.
Sexual politics in the global South: framing the discourse -- Saskia Wieringa and Horacio Sívori ; The rise of sex and sexuality studies in post-1978 China -- Huang Yingying ; The obscene modern and the pornographic family: adventures in Bangla pornography -- Hardik Brata Biswas ; Sexing the nation's body during the Cuban republican era -- Abel Sierra Madero ; Government and the control of venereal diseases in colonial Tanzania, 1920-60 -- Musa Sadock ; Violence and the emergence of gay and lesbian activism in Argentina, 1983-90 -- Diego Sempol ; Sexuality and nationalist ideologies in post-colonial Cameroon -- Basile Ndjio ; The 'lesbian' existence in Arab cultures: historical and sociological perspectives -- Iman Al-Ghafari ; 'Public women' and the 'obscene' body: an exploration of abolition debates in India -- Nitya Vasudevan ; Male homoeroticism, homosexual identity, and AIDS in Mexico City in the 1980s -- Alberto Teutle López ; Canons of desire: male homosexuality in twenty-first-century Keralam -- Rajeev Kumaramkandath ; Female criminality in Brazil: a study on gender and sexuality in a women's prison -- Fabíola Cordeiro ; Sexual pleasure and premarital sexual adventures of young women in Zimbabwe -- Tsitsi B. Masvawure.
Includes bibliographical references and index.
UCWS-2014-G-1672 donated by Zed Books.
Keywords: Sex -- Colonies; Sex -- Political aspects -- Cross-cultural studies; Sex -- Political aspects -- Africa -- History -- 20th century; Sex -- Political aspects -- Asia -- History -- 20th century; Sex -- Political aspects -- Latin America -- History -- 20th century; Sex role -- History